LPPA : lightweight privacy-preservation access authentication scheme for massive devices in fifth Generation (5G) cellular networks - Cao, Jin (2021)
Because of the requirements of stringent latency, high-connection density, and massive devices concurrent connection, the design of the security and efficient access authentication for massive devices is the key point to guarantee the application security under the future fifth Generation (5G) systems. The current access authentication mechanism proposed by 3rd Generation Partnership Project (3GPP) requires each device to execute the full access authentication process, which can not only incur a lot of protocol attacks but also result in signaling congestion on key nodes in 5G core networks when sea of devices concurrently request to access into the networks. In this paper, we design an efficient and secure privacy-preservation access authentication scheme for massive devices in 5G wireless networks based on aggregation message authentication code (AMAC) technique. Our proposed scheme can accomplish the access authentication between massive devices and the network at the same time negotiate a distinct secret key between each device and the network. In addition, our proposed scheme can withstand a lot of protocol attacks including interior forgery attacks and DoS attacks and achieve identity privacy protection and group member update without sacrificing the efficiency. The Burrows Abadi Needham (BAN) logic and the formal verification tool: Automated Validation of Internet Security Protocols and Applications (AVISPA) and Security Protocol ANimator for AVISPA (SPAN) are employed to demonstrate the security of our proposed scheme.